Polish Exiled Artist Jozef Berkman in Baikal Region in 60—70s of XIX Century - E. V. Semenov; V. A. Pokatsky (Научный диалог, 2022)
The issue of the life and creative activity of the Polish exiled artist — a participant in the Polish uprising of 1863—1864 Jozef Berkman is considered. The relevance of the study is due to the fact that, despite the significant number of drawings and paintings by Y. Berkman, today the facts of his life are practically unknown both in hard labor in the Nerchinsk mining district and in a settlement in the Irkutsk province. It is noted that the information found in a number of sources regarding the life of the artist in hard labor and settlement is often unreliable. The novelty of the study is seen in the fact that a reconstruction of the period of the artist’s life in 1864—1877 in the Baikal region is presented in the article. The authors have identified and introduced into scientific circulation materials from domestic and foreign archives, portraits of Polish exiles, painted by the artist in Transbaikalia and currently stored in museums in Poland. The authors reviewed the scientific literature on the topic of the study, analyzed the memoirs of Polish political exiles who served hard labor together with Y. Berkman and described his artistic activities.